2021
DOI: 10.1021/acs.macromol.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Chain Entanglement Induced by Thickness of Ultrathin Polystyrene Films

Abstract: The thickness effect on the relaxation behavior and chain entanglements was investigated for thin polystyrene films. By following the time evolution of the wetting ridge at the surface induced by a droplet of ionic liquid, the characteristic time (τ*) at which the ridge height started to change was obtained. Here, we demonstrated experimentally that the characteristic time was associated with the disentanglement time τ d , τ* ∼ τ d ∼ M w 3.4/Me 1.4, where Me denotes the entanglement molecular weight. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Shearing of linear chains causes a variety of conformational changes. Reported are not only stretching but also end-over-end tumbling and even chain collapse and compression. , Shown for linear chains by confinement at surfaces and interfaces, departure from a (time-averaged) spherical pervaded volume into ellipsoids decreases entanglement contacts. All mechanisms likely occur to different extent for an architecturally heterogeneous polydisperse blend. This idea agrees with simulations that show melt deformation causes a heterogeneous distribution of entanglements …”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shearing of linear chains causes a variety of conformational changes. Reported are not only stretching but also end-over-end tumbling and even chain collapse and compression. , Shown for linear chains by confinement at surfaces and interfaces, departure from a (time-averaged) spherical pervaded volume into ellipsoids decreases entanglement contacts. All mechanisms likely occur to different extent for an architecturally heterogeneous polydisperse blend. This idea agrees with simulations that show melt deformation causes a heterogeneous distribution of entanglements …”
Section: Concluding Discussionmentioning
confidence: 99%
“…Another detail to consider is that complex branch-on-branch architectures, as assumed for LDPE and LCB PP (see below), have no clear main-chain backbone. For molecules without a backbone, physically allowed conformational changes are deformations of (time-averaged) spherical pervaded volumes into ellipsoids. At least for linear chains, theory, simulations and experiments show when pervaded volumes distort into ellipsoid shapes by confinement at surfaces, the number of entanglements per molecule decreases. Thus, via these works, the idea of disentanglement by deformation occurs again.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of PS2k at the fracture position, which is approximately 15 nm apart from the substrate interface, was estimated to be 40–62% according to the ToF-SIMS results. Such a high fraction of PS2k will decrease the entanglement density in the interfacial region . Nevertheless, this value is much higher than expected from entropic segregation, in which the condensation of molecules should be in the size of the radius of gyration of the chain from the interface .…”
mentioning
confidence: 86%
“…Besides geometric engineering, traditional physical blending, and chemical methods, the nanoconfinement effect, introduced by blending semiconductors with elastomer and forming nanofibers in the elastomer matrix, has also been adopted to enhance the mechanical property of semiconductors without affecting their carrier mobility. In recent years, the rapid development of organic optoelectronic devices and soft and wearable materials has further stimulated researcher’s enthusiasm on the mobility of polymer films . Studies have found that the mobility of polymer thin films has a very important impact on the performance of organic photoelectric materials. It was known that nanoconfinement of polymers to nanometer-scale dimensions leads to special kinetic and thermodynamic properties due to the interface effect and finite-size effect, further influencing the performance of polymer thin films. , Nanoconfinement can change many physical properties of polymers, like lowering the glass transition temperature and modulus and increasing the mechanical ductility, which are desirable for stretchable materials.…”
Section: Fundamentals Of Conductive Polymers and Semiconductorsmentioning
confidence: 99%
“…In recent years, the rapid development of organic optoelectronic devices and soft and wearable materials has further stimulated researcher’s enthusiasm on the mobility of polymer films . Studies have found that the mobility of polymer thin films has a very important impact on the performance of organic photoelectric materials. It was known that nanoconfinement of polymers to nanometer-scale dimensions leads to special kinetic and thermodynamic properties due to the interface effect and finite-size effect, further influencing the performance of polymer thin films. , Nanoconfinement can change many physical properties of polymers, like lowering the glass transition temperature and modulus and increasing the mechanical ductility, which are desirable for stretchable materials. Thus, the confinement effect is important for improving the mechanical properties of flexible and stretchable devices.…”
Section: Fundamentals Of Conductive Polymers and Semiconductorsmentioning
confidence: 99%